Результати експериментальних досліджень балкової залізобетонної прольотної будови моста за етапами реконструкції - Рачкевич, В. С.; Семанів, Л. Я.; Кваша, В. Г.; Салійчук, Л. В.; Rachkevych, V.; Semaniv, L.; Kvasha, V.; Saliychyk, L. (Видавництво Львівської політехніки, 2018)
На мережі державних і місцевих доріг експлуатується значна кількість мостів із збірними або монолітними прольотними будовами малих і середніх прольотів, збудованих за ТП вип. 56. На даний час нормований термін їх експлуатації 25–30 р. перевищений у 2–2,5 рази і вони продовжують експлуатуватись при незадовільних їх експлуатаційних і техніко-економічних показниках. Тому для подальшої нормальної експлуатації вони потребують реконструкції з відновленням нормованих експлуатаційних показників. В даній роботі описана реконструкція одного з таких мостів через р. Прутець Яблунівський на км 218+872 автодороги Мукачеве-Львів. Представлені конструктивні рішення реконструкції, а також аналіз результатів експериментальних досліджень прольотної будови за етапами реконструкції

On the network of state and local roads, a significant number of bridges with precast or monolithic span structures of small and medium spans are constructed according to TP-56. At present time, their normalized period of exploitation of 25–30 years is exceeded in 2–2.5 times and they continue to be exploited with unsatisfactory exploitative and technical and economic parameters. Therefore, for further normal exploitation, they need to be reconstructed with the restoration of normalized exploitative parameters. In this work, the reconstruction of one of these bridges through the Prutets Yablunivskyi River on km 218 + 872 of the Mukachevo-Lviv highway is described. The constructive reconstruction decisions, the analysis of the results of experimental researches of the span structure during the reconstruction stages are presented. The suitability of the reconstructed span structure for further exploitation at the normalized temporary loads A15 and NK-100 has been confirmed. The possibility of extending the lifespan of reconstructed span structures constructed according to TP-56, comparable to newly built bridges was proved
The results of experimental researchs of the reinforced concrete beam span structure of the bridge by reconstruction stages
Keywords: залізобетонний міст; реконструкція; випробування; просторова робота; reinforced concrete bridge; reconstruction; tests; spatial work; 624.004.0125